Black Sea security : international cooperation and counter-trafficking in the Black Sea region - Houston, Fiona; Wood, W. Duncan; Robinson, Derek M. (NATO science for peace and security series. Human and societal dynamics, 2010)
The Black Sea is a vital strategic crossroads between Europe, Central Asia and the Middle East. Comprising at least ten countries, with diverse religious, cultural, political and economic backgrounds, the region was shaped historically by centuries of conflict between the Ottoman and Russian empires, and in the 20th century by the rise and dramatic collapse of the Soviet Union and the subsequent post-Cold War emergence of newly independent states. The region faces emerging security challenges of major international strategic interest, not least because 80% of all Russian gas destined for Europ.